The many faces of 'one' - Abd Razak, Dzulkifli (2009)
THE figure "one" has always been a fascination to almost everyone (no pun intended). Even from an early age, we are inculcated with the value that "one" is somehow the best. Being number one, for example, is highly valued, unique, and in many ways associated with some form of success, especially in aspects of competitions, which is today's jargon. This is, perhaps, because one, as a unit of "measure" in the pecking order, is the most simple to understand. In a community or organisation which is deeply hierarchical and elitist, to be number one is everyone's dream since it is synonymous with being endowed with power, real or perceived.